Term Rewriting System R:
[x, y]
g(c(x, s(y))) -> g(c(s(x), y))
f(c(s(x), y)) -> f(c(x, s(y)))
f(f(x)) -> f(d(f(x)))
f(x) -> x

Termination of R to be shown.

R
Dependency Pair Analysis

R contains the following Dependency Pairs:

G(c(x, s(y))) -> G(c(s(x), y))
F(c(s(x), y)) -> F(c(x, s(y)))
F(f(x)) -> F(d(f(x)))

Furthermore, R contains two SCCs.

R
DPs
→DP Problem 1
Instantiation Transformation
→DP Problem 2
Remaining

Dependency Pair:

G(c(x, s(y))) -> G(c(s(x), y))

Rules:

g(c(x, s(y))) -> g(c(s(x), y))
f(c(s(x), y)) -> f(c(x, s(y)))
f(f(x)) -> f(d(f(x)))
f(x) -> x

On this DP problem, an Instantiation SCC transformation can be performed.
As a result of transforming the rule

G(c(x, s(y))) -> G(c(s(x), y))
one new Dependency Pair is created:

G(c(s(x''), s(y''))) -> G(c(s(s(x'')), y''))

The transformation is resulting in one new DP problem:

R
DPs
→DP Problem 1
Inst
→DP Problem 2
Remaining Obligation(s)

The following remains to be proven:
• Dependency Pair:

G(c(s(x''), s(y''))) -> G(c(s(s(x'')), y''))

Rules:

g(c(x, s(y))) -> g(c(s(x), y))
f(c(s(x), y)) -> f(c(x, s(y)))
f(f(x)) -> f(d(f(x)))
f(x) -> x

• Dependency Pair:

F(c(s(x), y)) -> F(c(x, s(y)))

Rules:

g(c(x, s(y))) -> g(c(s(x), y))
f(c(s(x), y)) -> f(c(x, s(y)))
f(f(x)) -> f(d(f(x)))
f(x) -> x

R
DPs
→DP Problem 1
Inst
→DP Problem 2
Remaining Obligation(s)

The following remains to be proven:
• Dependency Pair:

G(c(s(x''), s(y''))) -> G(c(s(s(x'')), y''))

Rules:

g(c(x, s(y))) -> g(c(s(x), y))
f(c(s(x), y)) -> f(c(x, s(y)))
f(f(x)) -> f(d(f(x)))
f(x) -> x

• Dependency Pair:

F(c(s(x), y)) -> F(c(x, s(y)))

Rules:

g(c(x, s(y))) -> g(c(s(x), y))
f(c(s(x), y)) -> f(c(x, s(y)))
f(f(x)) -> f(d(f(x)))
f(x) -> x

Termination of R could not be shown.
Duration:
0:00 minutes